Comparação de métodos via solo e via demanda evaporativa para manejo de irrigação da cultura da soja safrinha - Nunes, Mario Santos (2014)
Irrigation must function adequately meet the water demands of crops so that they express their full productive potential. However, there are variations with the soil-plant-atmosphere relationship, interfering to determine the differences in crop yields, therefore, the use of technology and equipment is essential for good irrigation management. Techniques involving the use of agricultural instrumentation to determine irrigation depths are of great importance to scientific research. Regardless of the technique used, by soil or weather, is important an irrigation depth accurately determined and preferably easy. In order to compare methods of irrigation management, trying to verify the performance and sensitivity of these methods, from data retention curve of soil water, an experiment was installed in Fazenda Liberdade ,Santiago city (RS) in a Cruz Alta map unit, Haplustox, typical clay horizons A and B. Therefore, it was installed in an area of 88.64 ha , under a fixed central pivot, Watermark sensors to the method of handling the soil , such as humidity sensors , data collections with TDR and collection of soil samples for determination of gravimetric moisture by the electric furnace method. TDR data from the present study as a standard data depths of 7.6 , 10, 12, 20, 30 and 40 cm , and considering were analyzed . For management methods via weather a Irrigameter were installed along with a tank class A , methods via climate as Hargreaves & Samani , Thorthwaite , Camargo were also tested - 71 and Penman - Montheith . The results obtained with crude blade Watermark humidity sensors showed a very close to that obtained by TDR behavior compared to the class methods via climate Camargo and The Tank - 71 underestimated or overestimated results when compared to other methods . The results obtained by the methods of managing the soil are of greater precision than the methods via climate.